Asymmetric peak to average power ratio impacts on direct‐detected optical OFDM transmission link. Issue 11 (November 2016) - Won, Yong‐Yuk; Kim, Chang‐Hun; Han, Sang‐Kook; Seo, Dongsun
ABSTRACT: In this article, the impact of asymmetric peak to average power ratio (PAPR) of orthogonal frequency division multiplexing (OFDM) signal is investigated in direct detection OFDM transmission for the first time. The asymmetric PAPR is produced due to the positive definiteness of direct optical OFDM modulation. It gets bigger and bigger due to the generation of different time delay of each OFDM subcarrier, which is caused by chromatic dispersion. The performance of direct detection optical OFDM link in the presence of asymmetric PAPR is evaluated measuring error vector magnitude (EVM) of quadrature phase shift keying (QPSK) and 16‐qudrature amplitude modulation (QAM) symbols according to the optical transmission length and the transmission rate; 14% EVM (bit error rate of 10 −3 ) of QPSK symbol is observed at the optical transmission length of 400 km despite the usage of channel equalization as well as the insertion of cyclic prefix when the asymmetric PAPR of input optical OFDM signal is above 25 dB. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2662–2665, 2016